PENGARUH LITERASI KEUANGAN, SIKAP KEUANGAN DAN PENDAPATAN TERHADAP PERILAKU PENGELOLAAN KEUANGAN PELAKU UMKM - Ariyani, Asri Dwi; Hidayah, Nila; Munawaroh, Milatul; Setiorini, Kusumaningdiah Retno; Ahmad, Khamdani (Fakultas Ekonomi dan Bisnis Universitas Mataram, 2025)
Financial management is still an obstacle in developing MSME business capacity. This is due to the low level of financial literacy possessed by MSME actors as well as an attitude of awareness and responsibility that has not been carried out properly regarding financial management of business income. This research aims to determine the influence of financial literacy, financial attitudes and income on the financial management behavior of MSME players. This type of research is quantitative research. The research respondents were MSME actors in the culinary sector in Bantul Regency. Sampling was carried out using a purposive sampling technique with a sample of 102 respondents obtained in the study. The data used in this research is primary data, namely data from the results of the respondent's questionnaire answers. The analysis technique used is descriptive statistical analysis and multiple linear regression analysis. The research results show that (1) financial literacy has a significant effect on the financial management behavior of MSME actors; (2) financial attitudes do not have a significant effect on the financial management behavior of MSME actors; (3) income has a significant effect on the financial management behavior of MSME actors.